Rheumatic diseases in children and adolescents in the Russian Federation (2009—2010) - Rimma Mikhailovna Balabanova; N N Kuzmina; Sh F Erdes (Научно-практическая ревматология)
In pediatrics, rheumatic diseases (RD) are characterized by particularly severe social consequences. This investigation was undertaken to clarify the prevalence of RD from the 2009—2010 statistical data of the Ministry of Health and Social Development of the Russian Federation. Analysis of these data has led to the conclusion that the acute rheumatic fever situation is relatively favorable in Russia. As for musculoskeletal system diseases, patients with inflammatory RD are a small percentage among those with this pathology; however, they are critically ill and become disabled early and frequently despite the fact that the majority of novel highly effective drugs have not approved for use in children, which makes their timely use difficult. Most children with locomotor diseases suffer from non-inflammatory diseases. This shows the importance of measures for the prevention, early detection, and correction of acquired or inherited pathology of the joints and vertebral column.